Imported Asymptomatic Bancroftian Filariasis Discovered from a Plasmodium vivax Infected Patient: A Case Report from Singapore - Jean-Marc Chavatte; Roland Jureen (Case Reports in Infectious Diseases)
Human lymphatic filariasis is a vector-borne disease mainly caused by the parasitic nematode Wuchereria bancrofti and transmitted worldwide within the tropical and subtropical regions. Singapore was once endemic for bancroftian filariasis but recent reports are scarce and the disease is nearly forgotten. The case report presented here reports the incidental hospital laboratory finding of an asymptomatic microfilaremia in a relapsing Plasmodium vivax imported case during a malaria treatment follow-up appointment. The parasite was identified by microscopy as W. bancrofti and retrospective investigation of the sample collected during malaria onset was found to be also positive. Additional confirmation was obtained by DNA amplification, sequencing, and phylogenetic analysis of the mitochondrial cox1 gene that further related the parasite to W. bancrofti strains from the Indian region. Considering the large proportion of asymptomatic filariasis with microfilaremia, the high number of migrants and travellers arriving from the surrounding endemic countries, and the common presence of local competent mosquito vectors, Singapore remains vulnerable to the introduction, reemergence, and the spread of lymphatic filariasis. This report brings out from the shadow the potential risk of lymphatic filariasis in Singapore and could help to maintain awareness about this parasitic disease and its public health importance.